KOMUNIKASI PERSUASIF PENGURUS YAYASAN HUBBUL WATHAN KEPADA DOMATUR BEASISWA GUGUAK TABEK SAROJO - Wilda ‘Ashari Brilliant (ADISAM PUBLISHER, 2024)
The presence of many institutions in society reflects the high level of public confidence in the role of institutions as guides in daily life and fulfillment of basic human needs. The Hubbul Wathan Foundation was established in response to the limitations of education in Nagari Guguak Tabek Sarojo College, especially advanced education, and this initiative arose from the concerns of community leaders. The foundation seeks to raise funds to support talented children facing economic constraints so that they can continue their education. In attracting donors, Hubbul Wathan Foundation uses a persuasive communication approach by giving full confidence to donors through proposals containing valid data and through direct meetings between foundation administrators and donors. This approach is considered successful because counseling on the importance of zakat is delivered through advice without coercion. Thus, Hubbul Wathan Foundation has managed to build strong relationships with donors to support their scholarship programs